A VYGOTSKIAN PERSPECTIVE ON MULTICULTURAL EDUCATION: A SOCIAL-BASED LEARNING PROCESS IN THE MINANGKABAU COMMUNITY, WEST SUMATRA, INDONESIA - Moeis, Isnarmi; Indrawadi, Junaidi; Prasojo, Zaenuddin Hudi; Fatmariza, Fatmariza; Febriani, Rika (Paradigma: Jurnal Kajian Budaya, 2024)
Multicultural education and local wisdom function as crucial social assets in promoting unity within diverse societies. Indonesia, a country rich in ethnic diversity, possesses abundant local wisdom, particularly within the Minangkabau community of West Sumatra. This study examines the integration of Minangkabau local wisdom into the core elements of multicultural education, focusing on areas such as cultural awareness, sensitivity, cross-cultural communication, critical thinking, reflection, and cultural competence. Grounded in Vygotsky’s theory of learning as a process of social and cultural adaptation, this research adopts a qualitative methodology, utilizing in-depth interviews and focus group discussions for data collection. The analysis, carried out through coding, data reduction, and interpretation, focuses on the Minangkabau community in Sungai Sirah Village, Silaut District, a transmigration area in West Sumatra. The findings reveal that the Minangkabau community’s approach to multicultural education is deeply embedded in an awareness of the importance of active participation in multicultural settings. This process is reinforced by the leadership of local figures and enriched by the community’s historical, economic, and cultural heritage. The study offers valuable insights for developing a comprehensive model of multicultural education that can be applied in both formal and informal contexts, ultimately fostering social cohesion and inclusivity.